2017
DOI: 10.1177/0951484817726918
|View full text |Cite
|
Sign up to set email alerts
|

Business model framework applications in health care: A systematic review

Abstract: It has proven to be a challenge for health care organizations to achieve the Triple Aim. In the business literature, business model frameworks have been used to understand how organizations are aligned to achieve their goals. We conducted a systematic literature review with an explanatory synthesis approach to understand how business model frameworks have been applied in health care. We found a large increase in applications of business model frameworks during the last decade. E-health was the most common cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 222 publications
0
8
0
Order By: Relevance
“…For example, the results of the study conducted by Fredriksson et al showed that it is more appropriate to use different business frameworks for specific purposes. These frameworks should be in line with the context and purpose of using the technology [ 20 ]. However, the application of business models in the field of telehealth does not guarantee the success of new technologies, and before taking any action, legal issues and challenges related to licensing, compensation methods, liability, data sharing, and data protection must be resolved [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the results of the study conducted by Fredriksson et al showed that it is more appropriate to use different business frameworks for specific purposes. These frameworks should be in line with the context and purpose of using the technology [ 20 ]. However, the application of business models in the field of telehealth does not guarantee the success of new technologies, and before taking any action, legal issues and challenges related to licensing, compensation methods, liability, data sharing, and data protection must be resolved [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different business models have been proposed for the telehealth industry [ 1 , 19 ]. However, the findings of the research conducted by Frederickson et al showed that a business model and its components should be chosen based on the purpose of the technology and the context of use [ 20 ]. The results of other studies have indicated that patients, health care providers, payers, vendors, and other stakeholders play a key role in providing telehealth and telemedicine services.…”
Section: Introductionmentioning
confidence: 99%
“…Such a framework can play an important role in reducing risks and costs and can increase the likelihood of success in a telehealth business [ 22 ]. Moreover, it can facilitate developing a business plan, which, in turn, is a strategic tool for business success [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the Business Model Canvas (BMC) came forward as a valuable, wide-spread conceptual framework [26]. It is a commonly used business framework in the healthcare sector [27] and consists of nine building blocks, representing what value is provided to who, how this is done, and with what consequences [26,28]. See Fig 2 for the BMC.…”
Section: Phase 2: Designmentioning
confidence: 99%